EFFECT OF MALTODEXTRIN RATIO TO KLUTUK BANANA FRUIT EXTRACT (MUSA BALBISIANA COLLA) COMBINED WITH ITS PSEUDOSTEM EXTRACT ON ANTI-DYSENTERY GRANULE PERFORMANCE AND EFFECTIVITY - Kusuma, Sri Agung Fitri; Mita, Soraya Ratnawulan; Ermawati, Ratna Fitria (International Journal of Applied Pharmaceutics, 2018)
Objective: The objective of this study was to determine the best ratio of maltodextrin and extract concentration on performance of anti-dysentery granule containing Klutuk banana fruit extract (Musa balbisiana Colla) as an effective antimicrobial to treat dysentery caused by Shigella dysenteriae and combined with its pseudostem extract to supply potassium needed for supporting dehydration impact caused by dysentery. Methods: The dried fruit and pseudostem of the Klutuk banana plant were each extracted by maceration method. Each granule formula was optimized in different ratio of extract and maltodextrin concentration (1:2 (F1); 1:3 (F2); and 1:4 (F3) respectively. Then, the anti-shigellosis granule were formulated using the wet granulation method and evaluated for 30 d. The appearance of the granule, weight variation, loss on drying value, flowability, granule solubility, disintegration time, pH, and anti-dysentery activity of each formula was observed. The potassium content determination of each granule formula was done using an atomic absorption spectrophotometer method. Results: All formulated granules showed good flow properties and antidysentery activity. Concerning to the solubility, maltodextrin addition showed the increasing solubility of all formulated granule. The F3 achieved the best-improved granule characteristic and had good anti-dysentery effectivity, but had the lowest potassium content (0.362 g/l) among all formulas. The potassium content of F1 and F2 were 0.625 g/l and 0.444 g/l, respectively. Conclusion: Maltodextrin can improve the usefulness of granule that containing the Klutuk banana fruit and its pseudostem extracts in dysentery treatment and the dehydration impact.